Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1432-2277.2012.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic myocardial dysfunction does not affect survival in patients with cirrhosis

Abstract: Summary Left ventricular diastolic dysfunction (DDF) has been considered as a component of cirrhotic cardiomyopathy. The clinical significance of DDF in cirrhotics has not been clarified. We prospectively evaluated the echocardiographic‐Doppler, tissue‐Doppler (TDI) findings of left ventricular function and survival in cirrhotics with or without DDF. Seventy‐six cirrhotics without endogenous heart disease were included. DDF was diagnosed by mitral inflow Doppler parameters and diastolic myocardial velocities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 30 publications
(48 reference statements)
4
32
1
Order By: Relevance
“…Using the 2005 World Congress of Gastroenterology criteria, diastolic dysfunction was highly prevalent in our sample, in line with several previous reports . These criteria were based exclusively on mitral flow derived parameters, which are influenced not only by relaxation, but also by flow conditions.…”
Section: Discussionsupporting
confidence: 79%
“…Using the 2005 World Congress of Gastroenterology criteria, diastolic dysfunction was highly prevalent in our sample, in line with several previous reports . These criteria were based exclusively on mitral flow derived parameters, which are influenced not only by relaxation, but also by flow conditions.…”
Section: Discussionsupporting
confidence: 79%
“…A considerable number of studies have reported a direct relationship between the severity of diastolic dysfunction and severity of the liver disease, as reflected by the MELD-score, presence of ascites, and Child-Turcotte score, whereas some studies have been unable to detect a relationship with the degree of liver dysfunction [6,8]. As in the present study by Karagiannakis et al, several studies have reported a direct relation to prognosis, whereas other studies have failed to do so [6,8,14]. In a recent study by Ruiz-del-Arbol et al [8], the authors reported a direct relationship between variables obtained from tissue Doppler imaging (E/e 0 ) ratio and prognosis.…”
supporting
confidence: 44%
“…The prevalence of diastolic dysfunction among patients with cirrhosis varies according to the type of population and the severity of the disease, but there seems to be no relationship to etiology of cirrhosis. Different prevalences have been published ranging from 15 % to as high as 67 % [5,6,8,[14][15][16]. A considerable number of studies have reported a direct relationship between the severity of diastolic dysfunction and severity of the liver disease, as reflected by the MELD-score, presence of ascites, and Child-Turcotte score, whereas some studies have been unable to detect a relationship with the degree of liver dysfunction [6,8].…”
mentioning
confidence: 99%
“…Exclusion criteria were: Age under 18, known or suspected risk factors for cardiovascular disease (diabetes, systemic hypertension, smoking and obesity defined as body mass index > 30 kg/m 2 ), pulmonary major illness, severe anemia (Hg < 7 g/dL), severe systemic disease, hyperthyroidism and hypothyroidism, pregnancy and baseline electrocardiographic or echocardiographic evidence of structural heart disease, such as bundle branch block, regional wall motion abnormalities or valvular heart disease. Inclusion criteria were as strict as dictated by the defi nition discussed at the 2005 World Congress of Gastroenterology in Montreal and presented thereafter, so the cardiac dysfunction can be attributed to the CCM per se; moreover, they are similar to that described in other reports [26,27] . All the therapy interfering with cardiovascular system was suspended 24 h before the electrocardiographic and echocardiographic examinations not to alter the examinations' results.…”
Section: Study Populationmentioning
confidence: 61%